Evaluasi Dampak Truk Angkut Air terhadap Umur Fatigue Perkerasan dan Biaya Pemeliharaan Jalan - Vinsensius Budiman Pantas; Dewi Anastasia Ipah Wuwur (TIN: Terapan Informatika Nusantara, 2026)
Rigid pavement damage on Jalan Anggrek in Kupang City shows an increasing trend with the high intensity of commercial vehicles, especially water trucks. This study aims to evaluate the effect of water tanker truck traffic on the fatigue life of rigid pavement and its implications for road maintenance costs. The method used is a mechanistic-empirical approach based on the calculation of repeated axle loads, fatigue factors, and erosion factors in two traffic scenarios, namely with and without water trucks. Model validation is carried out by comparing the analysis results with the visual conditions of actual damage in the field, while model development continues with service life prediction and maintenance cost estimation using the cost per meter of crack unit. The results show that the presence of water trucks contributes significantly to increasing pavement erosion values, especially in the dual axle group, which has an impact on accelerating surface crack growth. In the scenario without water tankers, erosion values ​​are relatively low and indicate a slower degradation rate. The percentage of actual damage in the field of ±5% is still in the routine maintenance category, but the erosion value trend indicates a potential increase in the need for intervention in the future. Cost prediction models show that the dominance of water tanker trucks can increase accumulated maintenance costs by more than 30% over the long term compared to conditions without water trucks. Thus, water truck traffic has been shown to reduce pavement service life and increase road maintenance budget requirements, necessitating vehicle load control strategies and more adaptive structural planning on urban roads.